Endogenous competition and the underrealized reproduction of infectious diseases - Peng Huang; Zack W. Almquist; Carter T. Butts (Proceedings of the National Academy of Sciences, 2025)
Scientific inquiry about the transmissibility of infectious diseases is largely based on the basic reproduction number ( R 0 ) and its derivations. This paper describes a mechanism overlooked in most conventional analyses, in which a disease can endogenously “compete” with itself when multiple infectious individuals race to infect the same susceptible individual, thereby reducing the effective reproductive rate. Utilizing an empirically calibrated network epidemiological model of wild-type COVID-19 diffusion in its early pandemic, we show that the mechanism would be expected to reduce its reproductive rate by an average of 39%. Simulation experiments further identify different types of endogenous competition mechanisms and their relative effect sizes. We highlight the incorporation of endogenous competition mechanism as a necessary step in realistically modeling the reproduction process of infectious diseases.